What is TOETVA?What are the benefits of this technique compared to traditional thyroidectomy? - Voogd, Ana I. (Revista del Hospital Italiano de Buenos Aires, 2022)
Transoral endoscopic thyroidectomy by video-assisted vestibular approach (TOETVA) is a new and attractive technique for the surgical treatment of certain pathologies of the thyroid and parathyroid gland, whose greatest achievement is the absence of visible scar, is appropriate for selected patients and particularly motivated by aesthetic issues.
Keywords: TOETVA; thyroidectomy; scar; transoral surgery